REPRESENTASI PEREMPUAN AKTIVIS PAPUA BARAT DALAM FILM MAMAPOLITAN: KISAH PEREMPUAN PAPUA DI JAKARTA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This study aims to determine the use of signs and meanings that refer to the representation ofPapuan women activists in the film “MAMAPOLITAN: The Story of Papuan Women inJakarta”. This type of research is descriptive qualitative with a semiotic analysis approachmodel of Charles Sanders Pierce's trichotomy. The data sources were analyzed by primary andsecondary. The stages of data analysis carried out by researchers are by understanding the objectof research as the first step to understanding the content of the film, then dissecting the object ofresearch to examine each part and combine it with supporting words so that the message isconveyed in the documentary film MAMAPOLITAN: The Story of Papuan Women in Jakarta isobtained. The results of this study show several signs in the three scenes that refer to therepresentation of Papuan women activists in the film MAMAPOLITAN: The Story of PapuanWomen in Jakarta. Signs are analyzed using the concept of trichotomy which is divided into,(1) Objects consisting of icons, indexes, and symbols (2) Representamen consisting of qualisign,sinsign, and legisign (3) Interpretant consisting of rheme, decision, and argument. The results of the representation in the first scene show how Papuan women maintain their distinctive clothesamidst the hustle and bustle of the Metropolitan city. In the second scene, Papuan women boldlyvoice their massive freedom and right to live in their own land. In the third scene, Papuanwomen activists carry out demonstrations to maintain their identity in the form of traditionalclothes used by people who are not from Papua.